Sensing of Non-Volatile Memory Demystified - Ghosh, Swaroop; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book introduces readers to the latest advances in sensing technology for a broad range of non-volatile memories (NVMs). Challenges across the memory technologies are highlighted and their solutions in mature technology are discussed, enabling innovation of sensing technologies for future NVMs. Coverage includes sensing techniques ranging from well-established NVMs such as hard disk, flash, Magnetic RAM (MRAM) to emerging NVMs such as ReRAM, STTRAM, FeRAM and Domain Wall Memory will be covered. Provides a single-source reference to sensing technologies for non-volatile memories (NVMs), enabling readers to compare sensing performance of various options; Covers sensing techniques ranging from well-established NVMs such as hard disk, flash, Magnetic RAM (MRAM) to emerging NVMs such as ReRAM, STTRAM, FeRAM and Domain Wall Memory; Highlights challenges common among memory technologies and their solutions in mature technology, guiding innovation of sensing technologies for future NVMs.
Sensing of Spintronic Memories -- Sensing of Resistive RAM -- Sensing Techniques for Ferroelectric based Capacitors and Transistors for Non-Volatile Memory and Logic Applications -- Sensing of Phase Change Memory -- Conclusions. .
Keywords: Electronic circuits; Computer storage devices; Memory management (Computer science).; Electronics; Electronic Circuits and Systems; Computer Memory Structure; Electronics and Microelectronics, Instrumentation